Penile Fracture: Importance of Time in Management (Bangladesh Journal of Urology, 2025)
Background: Most Penile fracture is classically recognized as a urological emergency. Immediate surgical repair is the current standard of care with lower risks of complications. Although immediate surgery is advocated, timing of penile fracture repair can either be early (less than 24 hours from injury to presentation/surgery) or delayed (greater than or equal to 24 hours).Objective: To determine whether early surgical intervention has less postoperative complications than late intervention in patients presenting with penile fracture.Methodology:  This 15-month prospective analytical study conducted in the Department of Urology, Dhaka Medical College Hospital. Patients diagnosed with penile fracture undergoing surgery was the study population. A total of 24 patients were purposively selected as per inclusion and exclusion criteria. Their clinical history, physical examination, investigation reports & per-operative findings on surgical exploration were recorded. The patients were allocated into two groups according to the time of surgical intervention. Group A included the patients who were treated within 24 hours of incident and Group B included the patients who were treated with more than or equal to 24 hours of incident. The patients were followed up after 4 weeks, after 2 & 3 months. Result: There was no significant difference regarding mechanism of injury, side, site & length of injury, associated urethral injury & repairing difficulties. Wound infection & duration of hospital stay were more in delayed intervention group & that were statistically significant (p= 0.0244 & p=0.0163 respectively). During follow-up, delayed intervention group had statistically significant erectile dysfunction (p=0.0455 & p=0.048 respectively) after 2 & 3 months. Lastly, there was no significant difference regarding skin necrosis, hematoma, pyrexia in early post-operative period & palpable nodule, painful erection, chordee during follow up after 4 weeks, after 2 & 3 months.Conclusion: There was statistical difference between timing of penile fracture repair (early vs. delayed) regarding wound infection, duration of hospital stay & ED, which recommends early repair with less complications.Bangladesh J. Urol. 2024; 27(1): 55-61